Zehneria longiflora (Cucurbitaceae), a new species from Kenya - Wei, Neng; Miyawa, Daniel Odhiambo; David, Melly Kimutai; Ngumbau, Veronicah Mutele; Zhong, Zhi-Xiang; Mwachala, Geoffrey; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2017)
Zehneria longiflora, a new species of Cucurbitaceae from Nandi County, Kenya, is described and illustrated here. It is most similar to Z. oligosperma, but differs mainly by its longer receptacle-tube, stamens that are inserted at the middle of the receptacle-tube and with longer filaments, as well as characters of the male and female inflorescence.